1990
DOI: 10.2136/sssaj1990.03615995005400050019x
|View full text |Cite
|
Sign up to set email alerts
|

Humic Substances Formed during the Composting of Organic Matter

Abstract: Humic substances (HS) were extracted from separated cattle‐manure compost (CSM) at various stages of decomposition. Carbon‐13 nuclear magnetic resonance (13C‐NMR) and Fourier‐transform infrared (FTIR) spectroscopy measurements were performed on the purified humic acids (HA) as well as crude fiber and chemical analyses. Levels of HS extracted from the CSM samples doubled during the composting (from 377 to 710 g kg−1 organic matter [OM]). The HS were divided into: (i) HA, which increased from 184 to 457 g kg−1 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
138
2
9

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(157 citation statements)
references
References 0 publications
8
138
2
9
Order By: Relevance
“…Adani et al (1999) concluded that although the amount of HAlike relatively increased during composting (in g kg-1 VS), the absolute amount of HA-like decreased, especially at the start of the composting process. Chefetz et al (1998) showed that the coating material bound to core-HA-like was degraded during the composting process and Inbar et al (1990) suggested that HA-like was formed from partially degraded constituents of composted parent materials. Therefore, the humification process can be interpreted as the elimination of interference materials (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Adani et al (1999) concluded that although the amount of HAlike relatively increased during composting (in g kg-1 VS), the absolute amount of HA-like decreased, especially at the start of the composting process. Chefetz et al (1998) showed that the coating material bound to core-HA-like was degraded during the composting process and Inbar et al (1990) suggested that HA-like was formed from partially degraded constituents of composted parent materials. Therefore, the humification process can be interpreted as the elimination of interference materials (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Ten g (dry-weight basis) of compost (at natural moisture level) was placed in polyethylene centrifuge bottles, 100 mL NaOH (0.01 M) [18] 20 ) and 24 h (Et 24 ). At the end of each extraction time, the sides of the bottles were washed with distilled water, and the mixture centrifuged at 7500 rpm for 12 min.…”
Section: Methodsmentioning
confidence: 99%
“…Total organic carbon was determined using loss on ignition method [10] . The carboxylic-COOH, phenolic-OH functional groups and total acidity were determined by the method described by Inbar et al [14] . E 4 /E 6 was determined using E 4 /E 6 ratio [13] .…”
Section: Methodsmentioning
confidence: 99%